PEMANFAATAN BERBAGAI JENIS MULSAUNTUK PERTUMBUHAN DAN PRODUKSI TANAMAN UBI JALAR UNGU (Ipomoea batatas L) - Veronika Puken; Adrianus Adrianus; joana mendes; Rangga Kusumah (Musamus Journal of Agrotechnology Research, 2022)
ABSTRACT purple sweet potato (ipomoea batatas L) is a local commodity that has the potential to be developed to meef food. Shortages. Merauke is one of the best sweet potato producers, so to further increase the production of purple sweet potatoes, cultivation techiques are needed using various types of mulch. This study aims to determine the effect of mulching on the growth and production of purple sweet potato (Ipomoea batatas L). This research was conducted for 4 months, from April to August 2021 in Mandala Village, Merauke Regency, using a randomized block design (RAK) with 4 treatments, 6 replications. The results showed that the application of silver black plastic mulch and imperata mulch had a significant effect on the number of leaves at the age of 1 and 2 weeks, and the observation of the number of branches had a significant effect on the age of 4 weeks, 5 weeks, and 6 weeks, and tuber length, number of tubers and tuber diameter. From various treatments of silver black plastic mulch, rice straw mulch, and weed mulch, it was seen that the treatment of Imperata mulch gave above-average yields during the generative period with a mulch thickness of 5 cm. Keywords: Silver Black Plastic, Rice Straw, Imperata, Purple, Sweet Potato.